Organizational behavior - Schermerhorn, John R. (John Wiley & Sons, 2005)
Some topics include management functions; the social sciences; helping employees balance work and other responsibilities; improving people skills; improving customer service; motivational concepts; communication; power and politics; conflict and negotiation; culture; and stress management. Globally accepted and written by one of the most foremost authors in the field, this is a necessary read for all managers, human resource workers, and anyone needing to understand and improve their people skills.